Studi kinetika proses atmospheric pressure acid leaching bijih laterit limonit menggunakan larutan asam nitrat konsentrasi rendah - Kevin Cleary Wanta; Felisha Hapsari Tanujaya; Ratna Frida Susanti; Himawan Tri Bayu Murti Petrus; Indra Perdana; Widi Astuti (Jurnal Rekayasa Proses, 2018)
Kinetics study of atmospheric pressure acid leaching (APAL) process is indispensable for extractor design in an industrial scale. So far, the kinetic model used for this process is the shrinking core model. In this study, the shrinking core model was evaluated against experimental data for laterite leaching process using a solution of low concentration nitric acid (0.1 M). Variations in temperature and particle size were carried out at 303–358 K and <75–250 microns. Other operating conditions, such as pulp density, stirring speed, and time were kept at 20% w/v, 200 rpm, and 120 minutes, respectively. The model evaluation results showed that the shrinking core model was not suitable for this process because the process controlling stage is not just one stage only.